Effect of polymer modification on bitumen rheology: A comparative study of bitumens obtained from different sources - Ozdemir, Ahmet Munir; Yalcin, Beyza Furtana; Yilmaz, Mehmet (De Gruyter Poland Sp Z O O, 2025)
The rheological and mechanical properties of bituminous binders vary significantly depending on the crude oil source. Consequently, the response of binders from different sources to polymer modification also differs. This study compares the rheological performance of B160/220 penetration-grade binders sourced from the Turkey-Batman and Iraq-Lanaz refineries, modified with styrene-butadiene-styrene (SBS), the most widely used polymer additive. To evaluate high-temperature performance, performance grade and frequency sweep tests were conducted using a dynamic shear rheometer. In addition to experimental assessments, the rheological behavior of the binders was analyzed using the Christensen-Anderson, Cross, and Carreau-Yasuda models. Time-temperature superposition principle master curves were generated to characterize their viscoelastic behavior. Zero shear viscosity (ZSV) values were determined using the Cross and Carreau-Yasuda models to examine the impact of polymer modification on binder viscosity. The findings indicate that the initial rheological properties of bitumen significantly influence its response to SBS modification. For instance, the G*/sin delta value increased by up to 199% at 64 degrees C with 4% SBS addition, while the softening point rose by 9.5 degrees C compared to unmodified binders. Modelled ZSV values showed more than a sevenfold increase in some cases, especially in Iraqi binders. On the other hand, at -18 degrees C, the m-value dropped to 0.282 in the B-SBS4 binder, indicating a potential risk of low-temperature cracking. While polymer modification improved the rheological properties of both bitumen types, its effectiveness varied depending on the source.
Keywords: bitumen; rheology; styrene-butadiene-styrene